The effects of taxation on the location decision of multinational firms: M&A vs. Greenfield investments - Shafik Hebous; Martin Ruf; Alfons J. Weichenrieder (Center for Economic Studies and ifo Institute (CESifo), 2010)
In this study, we estimate the impacts of differences in international tax rates on the probability of choosing a location for an affiliate of a multinational firm. In particular, we distinguish between the tax sensitivity of Greenfield and M&A investments. Based on a novel firm-level dataset on German outbound FDI, we find evidence that location decisions of M&A investments are less sensitive to differences in tax rates than location decisions of Greenfield investments. According to our logit estimates, and after controlling for firm and country-specific characteristics, the tax elasticity for Greenfield investments is negative and in absolute value significantly larger than that associated with M&A investments. This finding is consistent with a (partial) capitalisation of taxes in the acquisition price when the FDI project takes the form of M&A.
Keywords: H25; H73; F23; 330; FDI; corporate taxation; location; M&A; Greenfield; Multinationales Unternehmen; Direktinvestition; Deutsch; Standortwahl; Übernahme; Unternehmensbesteuerung; Steuerwettbewerb; Deutschland; Welt